Investigating Terminologies in Teaching Literature: A Corpus Study - Agista Nidya Wardani; Adityo Adityo (STKIP Singkawang, 2021)
Regarding the literature subjects provided by the English Language Education Department, University of Muhammadiyah Malang, some students conduct researches on literature in their thesis. They find difficulties in doing the research as lacking of experience in discussing the thing and lacking vocabulary in describing terminologies. This research was designed to help the students whose major is English Education to maintain their study, especially on teaching English literature by finding out the terminologies in teaching literature books in terms of their frequency, example of their use, and meaning (in context). The objects of this research are Teaching and Learning English Literature by Ellie Chambers and Marshall Gregory, and Teaching Holocaust Literature and Film by Robert Eaglestone and Barry Langfor (Ed.) talking about teaching literature. The research method is document analysis. In number, there is no significant difference between them. No literary terminology that is more than 250 words. Beside, since they talk the same scope, the meanings of the terminologies are the same. Further, both present different use of terminologies. In some sentences, the terminologies are used to explain something closer to literature, yet in some other sentences, the terminologies are used to describe or explain the things related to teaching literature.